Facile synthesis of tetrahedral Ag3PO4 mesocrystals and its enhanced photocatalytic activity - Dong, Pengyu (2015)
A novel and rapid strategy has been developed to synthesize tetrahedral Ag3PO4 mesocrystals with the help of surfactant oleic acid. Homogeneous Ag3PO4 tetrahedron with average apex-to-apex length of 1.1 μm could be synthesized under optimized conditions. Oleic acid is considered to be essential for the formation of this homogeneous tetrahedral morphology. The as-prepared tetrahedral Ag3PO4 mesocrystals could be formed through the close-packed assembly of Ag3PO4 nanoparticles, thus the formation of tetrahedral Ag3PO4 mesocrystals is explained by the oriented aggregation mechanism based on time-dependent experiments. Furthermore, the obtained tetrahedral Ag3PO4 mesocrystals exhibit enhanced visible-light photocatalytic degradation of methylene blue (MB) and methyl orange (MO) solutions compared to the reported micro-sized spherical Ag3PO4 particles with high photocatalytic performance.